(untitled) (Asian Journal of Social Science Studies, 2022)
The alienation of labour, the alienation of needs and the alienation of consumption are three forms of alienation, and three stages in which the degree of alienation continues to increase. In terms of their transmutation history, the three alienations are the composite products of different historical periods, levels of productivity and degrees of industrialisation. In terms of their generative logic, labour alienation is the starting point for the emergence of a series of alienating forces; need alienation is the inevitable product of labour alienation and the necessary intermediary for the emergence of consumer alienation; and consumer alienation is the joint effect of labour and need alienation.